Results of magnetotelluric survey for studying geothermal system in the Bang area, Quang Binh province - Tuyen, Doan Van; Vu, Tran Anh; Phong, Lai Hop; Si, Le Van; Dat, Pham Ngoc; Ninh, Duong Thi; Toan, Dinh Van; Quang, Nguyen Thi Hong (Vietnam Journal of Earth Sciences, 2015)
This paper presents the first results from the application of magnetotelluric method (MT) using the new equipment MTU 2000 (Canada) and analysis software to investigate the structure of geothermal area around the Bang hot water source (Quang Binh province). Results of data analysis by MT 1D and 2D models to a depth of 20 km show low resistivity zone in the southwest of Bang hot water (100°C) and allow for interpreting the structural elements of athehydro- geothermal system. This includes a very low resistivity layer at depth of 2 km suggesting a clay cap (heat resistive shield), a relatively low resistivity zone at depth ≥ 2 km reflecting fractured rocks containing geothermal fluid and hot steam. A lower resistivity body at depth of 12-14 km located about 1.5 km from the hot water source indicates the existence of a heat source or a hot mass of intrusive magma., commonly thought to be sources of typical hydro- geothermal systems potential for energy exploitation. The obtained results not only provide new information for better understanding geothermal resource in the surveyed area, but also point out the methods and technology needed to improve the effectiveness for assessing potential of geothermal resources elsewhere in Vietnam. References Bản đồ Địa chất và khoáng sản Việt Nam tỷ lệ 1:1.000.000. Cục Địa chất và Khoáng sản Việt Nam xuất bản 2004. Lưu trữ Địa chất. Cumming W., 2009: Geothermal resource conceptual models using surface exploration data. In: proceedings, 34th workshop on geothermal reservoir engineering, Stanford University. Data Processing User guide. Phoenix Geophysic Ltd. 2005, 201p. Di Pippo R., 2012: Geothermal Power plant. Principles, applications, case studies. 3rd edition. Elseverdirect, 579p. Doan Van Tuyen, Tran Anh Vu, Nguyen Thi Kim Thuong, 2014: Geochemical Characteristics of Geothermal Hot Water Sources on the Territory of Vietnam. Proceeding, Thirty-Eighth Workshop on Geothermal Reservoir Engineering Stanford University, Stanford, California, February 24-26, 2014 SGP-TR-202. Duchkov A.D., Nguyen Trong Yem, Dinh Van Toan, and Trinh Viet Bac, 1992: First estimations of heat flow in northern Vietnam. Soviet Geology and Geophysics, Vol. 33, No. 5, pp 92-96. Flynn T., Quy H. H., 1997: Assessment of the geothermal resources of Socialist Republic of Vietnam. Geothermal resources Council Transactions, vol.21, 341-345. IGA report, 2013: Geothermal Exploration best practices: A Guide to resource data collection, analysis, and presentation for Geothermal projects. He Lijuan, 1999: Analysis of heat flow along a transect across the South China Sea. Geothermal Training Programme, Reports 1999, Number 5, 125-140. Hoang Huu Quy, 1998: Overview of the Geothermal potential of Vietnam. Geothermics, Vol.27, n.1, 109-115. Koenig J. et al., 1981: Evaluation of the potential for Geothermal Energy Resources in the SR of Vietnam. Berkeley, CA. Kulinich G.G., Zabolotnikov A.A, Markov Yu., 1989: Cenozoic evalution of the Earth crust and orogeny in South- Eastern Asia (Tiếng Nga). MTU2000: User guide. Phoenix Geophysic Ltd. 2000, 36p. Munoz Gerard, 2014: Exploring for Geothermal Resources with Electromagnetic Methods. Surv Geophys (2014) 35:101-122, Springer, DOI 10.1007/s10712-013-9236-0. Pellerin et al., Johnston M, Hohmann W., 1996: A numerical evaluation of electromagnetic methods in geothermal exploration. Geophysics 61(1996):121-130. Thomas Mathews, et al., 2008: Study on the sozio-economic framework for the use Geothermal energy in Vietnam. Proceedings of the 8th Asian Geothermal Symposium, Hanoi. Trần Huyên, Trương Minh, Nguyễn Tiến Bào, 1999: Về chế độ địa nhiệt ở các bể trầm tích thềm lục địa Việt Nam. Tạp chí Kinh tế Địa chất và Nguyên liệu khoáng. Cục Địa chất và Khoáng sản Việt Nam. Số 18 tháng 2 năm 1999, tr.16-25. Võ Công Nghiệp (chủ biên), 1998: Danh bạ các nguồn nước khoáng và nước nóng Việt Nam. Cục Địa chất và Khoáng sản Việt Nam. Hà Nội, 300tr. Zhdanov M., 2009: Geophysical Electromagnetic Theory and Methods. Methods in Geochemistry and Geophysics, Volume 43. ISSN: 0076-6895 Elsevier, 831pp. WinGLink User guide. Geosystem 200, 182p. www.geosystem.net.